2021
DOI: 10.1093/ijpp/riab024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticoagulant therapy management in a teaching hospital in Tunisia: information and education for vitamin k antagonist newly treated patients need to be improved

Abstract: Objective The objective of this study was to assess the level of Vitamin K antagonist (VKA) therapy knowledge among VKA newly treated patients. Methods Questionnaire-based interviews were administered in a university hospital to VKA newly treated patients covering both cognitive (i.e. indication, route of administration, treatment monitoring and side effects) and know-how (i.e. safety precautions, what affects anticoagulant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Consistent with a previous Tunisian study, a moderate negative correlation was found between patients' knowledge of VKA therapy and age [7]. Elderly patients and patients with lower education were more likely to have poor knowledge of the treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with a previous Tunisian study, a moderate negative correlation was found between patients' knowledge of VKA therapy and age [7]. Elderly patients and patients with lower education were more likely to have poor knowledge of the treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Only onethird of the study patients were aware of the importance of VKA therapy monitoring and one-fifth knew how VKA treatment should be monitored. This lack of knowledge may be due to the fact that over one-third of the patients were illiterate [7]. Yet, other investigators reported similar findings among patients with a higher level of education [4].…”
Section: Discussionmentioning
confidence: 91%